SEJARAH PERTUMBUHAN DAN PERKEMBANGAN PENDIDIKAN ISLAM DI INDONESIA - Yahdi, Muhammad (Jurnal Pendidikan Kreatif, 2023)
Islamic education in Indonesia in its early days was non-formal which was adapted to the conditions of society, namely by conducting interpersonal interactions that took place on various occasions and fields such as trade. Interaction gives a positive value with all elements in society. For Islam, the introduction of various religious sciences and knowledge has begun, the attitude and personality emerges among each person.